Pembelajaran Matakuliah Pengauditan Dalam Sebuah Kajian: Ada Apa Dibalik Problematika Pembelajaran Daring ? - ginting, Rafles; Tungga Dewi, V. Ananta Wikrama (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This research was conducted with the aim of knowing the problems that occurred in lectures during the pandemic, as well as finding an alternative in overcoming the problems of lectures. The alternative is studied further in a learning strategy. The theory used in this research is Behavioristic Learning Theory. This research was conducted on Accounting Study Program students at Tanjungpura University using qualitative research methods, case study approaches, where the research conducted resulted in several findings related to problems that occurred in brave learning during the pandemic. Some of the problems found during online learning, namely; miscommunication between lecturers and students, student ethics, lack of commitment and responsibility. To produce good output, an effective learning process must be carried out. The learning process is determined by the learning strategy implemented by the lecturer. Based on these problems, it is an implementation of learning strategies as an effort to handle the problems of the lectures carried out.